EVANGELISM STRATEGY THROUGH MEDICAL MISSIONARY WORK IN SPREADING THE GOSPEL BASED ON LUKE 10:9 - Landu, Serilius Ariyanto Kota; Alvyn C. Hendriks (Kirana Publisher, 2024)
Evangelism through medical missionary work has become an integral strategy in spreading the teachings of the Gospel, in line with the great mandate given by Jesus to His disciples. This paper aims to explore in depth the relationship between health and the Gospel, by critically reviewing the history, goals and methods of medical missionary work, as well as analyzing evangelism strategies that can be applied in this context. By using a qualitative approach to various relevant literary sources, this research provides a comprehensive picture of Peter Parker's contribution as one of the pioneer medical missionaries and his impact on the development of evangelism in various regions. In addition, this research also highlights the importance of thorough preparation and appropriate qualifications for medical missionary workers, including a deep understanding of the culture and social context in which they serve.